(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
the article analyzes the mechanisms of the policy used by the Russian Empire in the second half of the 19th century and the beginning of the 20th century to strengthen its colonial benefits in Turkestan. The tsarist authorities did not intend to develop the native language as a literary language or to make the local people literate, recommending the use of the native language of the local population in the education of the local people of Turkestan. They intended to use the educational process primarily as a weapon in the benefits of tsarism. The colonialists emphasized the need to create wide opportunities for the promotion of new ideas among the local population, to organize schools that would give the local population an understanding of and promote the Christian religion, and to instill respect for Russians, and to train teachers. The program for organizing public education in Turkestan, based on the proposal of the local people to use their native language and the Cyrillic alphabet, was mainly aimed at moving the local people away from the Arabic alphabet, the Tatar language, and, in general, Islamic enlightenment, and bringing them closer to the Christian religion.